Microencapsulated extracts from Azadirachta indica seeds: Acquisition, characterization, and use in controlling Helicoverpa armigera. Issue 10 (12th July 2021) - Bezerra, Debborah Gonçalves; Devilla, Ivano Alessandro; da Conceição, Edemilson Cardoso; Czepak, Cecília; Albernaz Godinho, Karina C.; Caramori, Samantha Salomão; Portela, Roberto Campos; de Paula, Joelma Abadia Marciano
Abstract: Biodegradable insecticides of Azadirachta indica A. Juss (Meliaceae) can be sustainable alternatives for agriculture. The goal of this study was to develop spray-dried microencapsulated extracts from A. indica seeds and to evaluate their effects in vitro on Helicoverpa armigera Hübner. Five polymeric matrices based on different proportions of gum arabic and maltodextrin were produced and characterized by evaluating photostability profile, drying yield, encapsulation efficiency, water activity, and azadirachtin content. In the photostability study, sample 3 showed the lowest loss of azadirachtin at the end of 15 days (62.90%). In the bioassays, the deterrence percentage was 100%. It was observed that in a 15-day period there was 100% mortality among the caterpillars that had a diet containing about 288 to 576 μg.mL −1 of microencapsulated extract. The microencapsulated extract from A. indica seeds presented increased azadirachtin photostability and showed potential as a bioinsecticide in the control of H. armigera .